Pengaruh Media Tanam Terhadap Pertumbuhan Tanaman Hortikultura Pada Berbagai Komposisi Dan Kondisi Lingkungan Terkendali - Choirunnisa` (Jurnal Ilmu Pendidikan Biologi dan IPA, 2026)
Growing media is one of the key factors influencing the growth of horticultural crops, particularly under controlled environmental conditions. This study aimed to analyze the effects of different growing media compositions on the growth of horticultural plants in a controlled environment. The research employed an experimental method using a completely randomized design, with various growing media compositions as treatments. Growth parameters observed included plant height, number of leaves, and plant biomass. The results showed that differences in growing media composition had a significant effect on all observed growth parameters. Mixed growing media containing soil, organic matter, and porous materials produced better plant growth compared to single-media treatments. The controlled environment played an important role in minimizing external environmental influences, allowing plant responses to growing media to be observed more accurately. It can be concluded that selecting appropriate growing media composition is essential to support optimal growth of horticultural crops and can be applied to efficient and sustainable cultivation systems.